2017
DOI: 10.14310/horm.2002.1719
|View full text |Cite
|
Sign up to set email alerts
|

The impact of thyroid autoimmunity (TPOAb) on bone density and fracture risk in postmenopausal women

Abstract: ObJeCTIVe: Skeletal development, linear growth, cartilage biology and bone turnover are highly dependent on the activity of thyroid hormones. Thyroid dysfunction affects the skeleton, and autoimmune thyroid disease, manifesting as a chronic inflammatory condition, may be an important contributing factor to impaired bone quality in these patients. MATeRIAlS AND MeTHODS: Measurement of TSH, FT4, TPOAb and bone mineral density and FRAX score calculations were performed in 189 postmenopausal women (110 euthyroid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…It obviously supports the assumption that autoimmunity might represent an important driver in pathogenic bone loss [15]. Decreased BMD has been found in patients with SLE [12], chronic thyroiditis [13] and autoimmune hepatitis [14] in previous studies. Although declines in BMD in patients with SLE might also be due to the SLE-related glucocorticoid treatment, several studies have pointed out that autoantibodies were able to induce osteoclast differentiation and activation and to alter bone mineral content.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It obviously supports the assumption that autoimmunity might represent an important driver in pathogenic bone loss [15]. Decreased BMD has been found in patients with SLE [12], chronic thyroiditis [13] and autoimmune hepatitis [14] in previous studies. Although declines in BMD in patients with SLE might also be due to the SLE-related glucocorticoid treatment, several studies have pointed out that autoantibodies were able to induce osteoclast differentiation and activation and to alter bone mineral content.…”
Section: Discussionsupporting
confidence: 83%
“…Notably, decreased BMD was found in patients with various autoimmune diseases, which include systemic lupus erythematosus [12], serologically suspected chronic thyroiditis [13], and autoimmune hepatitis [14]. These observations are in line with the conclusion of a recent review that autoimmunity seemed to represent an important driver in pathological bone loss [15].…”
Section: Introductionsupporting
confidence: 82%
“…Different patterns of associations between BTMs and thyroid measures by the status of thyroid autoantibodies suggest that thyroid autoantibodies should be considered in the regulation of bone metabolism by thyroid hormones. Although one study reported that the presence of TPOAb is a potential marker of higher fracture risk in these patients ( 52 ), associations between BTMs and TPOAb or TgAb status have rarely been assessed in the human population. In the current observational study, while no direct associations were observed between BTMs and thyroid autoantibody status, the associations with TSH, FT 4 , SPINA-G D , SPINA-G T , TTSI and TSHI appeared to be influenced by ATA status.…”
Section: Discussionmentioning
confidence: 99%
“…PTC patients with severe osteoporosis have a higher prevalence of TPO-Ab than patients without severe osteoporosis [ 10 ]. The presence of TPO-Ab is associated with osteoporotic fractures in euthyroid postmenopausal women [ 26 ]. On the other hand, the risk of thyroid cancer is not related to TPO-Ab levels but is associated with Tg-Ab levels [ 27 ].…”
Section: Discussionmentioning
confidence: 99%